We have the next two equations
![\begin{cases}4x-6y=13 \\ -5x+2y=5\end{cases}](https://img.qammunity.org/2023/formulas/mathematics/college/zwd8do6ugfx3gaa7cxkr9yrblhd4763tke.png)
And we must find the result of subtracting the second equation from the first.
Since we need to subtract the second equation from the first we must solve the next
equation 1 - equation 2
So, first we must negate all the second equation terms
![\begin{gathered} -1(-5x+2y)=-1(5) \\ 5x-2y=-5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jcvyozih4m9sfp7odg0qm4xeacy83g67mf.png)
Then, we must add the result to the first equation
![\begin{gathered} 4x-6y=13 \\ 5x-2y=-5 \\ ----------- \\ 9x-8y=8 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/oct0vas0k1s2tkogj77klv0pkxnwgbwhza.png)
Finally, the result of subtracting the second equation from the first is
![9x-8y=8](https://img.qammunity.org/2023/formulas/mathematics/college/hi4si8m69qy8p5m4lut8hg6rpkkkxm5kki.png)
ANSWER:
9x - 8y = 8